ON THE DEVELOPMENTOF THE STATE ACCOUNTINGIN ANCIENT EGYPT - Irina V. Malykhina (Статистика и экономика, 2016)
The study of the origin and development of the earliest forms of accounting in the initial epoch of ancient Egyptian state formation is faced with the problem of aninsufficient number of artifacts. The major role in the history of accounting during the first five dynasties plays Palermo Stone. A careful study of the chronicles of the Palermo stone allows us to trace the changes in accounting operations, covering religious, military, political and economic areas in the Early Dynastic period of the Egyptian society.